2017
DOI: 10.1155/2017/9205834
|View full text |Cite
|
Sign up to set email alerts
|

Single-Session Combined Anterior-Posterior Approach for Treatment of Ankylosing Spondylitis with Obvious Displaced Lower Cervical Spine Fractures and Dislocations

Abstract: For patients with AS and lower cervical spine fractures, surgical methods have mainly included the single anterior approach, single posterior approach, and combined anterior-posterior approach. However, various surgical procedures were utilized because the fractures have not been clearly classified according to presence of displacement in these previous studies. Consequently, controversies have been raised regarding the selection of the surgical procedure. This study retrospective analysis was conducted in 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 15 publications
(13 reference statements)
0
11
0
2
Order By: Relevance
“…Combined surgery can provide strong internal fixation, which allows patients to exercise early for functional recovery and thus reduces the incidence of pulmonary infection associated with long-term bed rest. Although combined approaches are the most invasive option, in cases of ASCF, many studies have shown strong support for this type of treatment [28][29][30][31][32] . This FEM study also found that the combined anterior and posterior approach has the minimal RoM change at the fractured level (C5/6) and the smallest implant MS compared with either approach alone; even 1-level combined fixation provides better stability than 5-level posterior-alone fixation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined surgery can provide strong internal fixation, which allows patients to exercise early for functional recovery and thus reduces the incidence of pulmonary infection associated with long-term bed rest. Although combined approaches are the most invasive option, in cases of ASCF, many studies have shown strong support for this type of treatment [28][29][30][31][32] . This FEM study also found that the combined anterior and posterior approach has the minimal RoM change at the fractured level (C5/6) and the smallest implant MS compared with either approach alone; even 1-level combined fixation provides better stability than 5-level posterior-alone fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical approaches for ASCF include anterior spinal fusion (ASF) 23 , 24 , posterior spinal fusion (PSF) 11 , 25 27 , and anterior–posterior spinal fusion (APSF) 28 32 , each of which achieves partial therapeutic success. However, a consensus regarding the surgical approach and implant length and density has not been achieved, as the present available literature mainly consists of low-level evidence case series or case reports with small samples 23 , 27 , 30 .…”
Section: Introductionmentioning
confidence: 99%
“…IAPs of lumbar vertebrae are located on the anterior and lateral convex. They cover their anterolateral surface, which possesses inferior articular facets [19]. Thus, we hypothesized that the hypertrophy of IAP might have a close relation to facet joint arthritis and CLSS.…”
Section: Discussionmentioning
confidence: 99%
“…Our interpretation of such an association is based on our understanding that the IAP hypertrophy process begins with mechanical friction during lumbar rotation, extension, and flexion. Because the inferior articular facet meets the superior articular facet at the posterior and medial concavity of the adjoining surface [19], these frictions can exert continuous pressure on zygapophyseal joints and alter morphological features of IAP, leading to a high degree of abrasion [20]. Burke et al have reported a case of spinal cord trauma caused by direct transmission of force from an ostectomy to a symptomatic ossified ligamentum flavum during resection of an IAP [21].…”
Section: Discussionmentioning
confidence: 99%
“…Распространенность анкилозирующего спондилита (АС) среди населения достигает 0,3 % [10, 13], а одним из наиболее частых проявлений заболевания является поражение центральной (ЦНС) и периферической нервной системы (ПНС) [9,11], что в первую очередь обусловлено патологией позвоночника [8]. К главным причинам тяжелой нейропатии у больных АС относятся подвывихи и микропереломы позвонков [6,7,16], а также демиелинизирующая патология [4]. Необходимо отметить, что для таких пациентов свойственны нарушения вегетативного звена нервной системы [14], которые прежде всего затрагивают ее парасимпатическую составляющую [12].…”
Section: Introductionunclassified